2018
DOI: 10.5599/admet.6.1.497
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution rate of ciprofloxacin and its cocrystal with resorcinol

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…This dissolution rate behavior is similar to that observed in a preliminary study conducted for a Ciprofloxacin-resorcinol cocrystal [30]. In fact, both APIs belong to the same family, and they have similar structures and pK a values, so similar dissolution rate behavior was expected.…”
Section: Intrinsic Dissolution Rate Studysupporting
confidence: 86%
See 2 more Smart Citations
“…This dissolution rate behavior is similar to that observed in a preliminary study conducted for a Ciprofloxacin-resorcinol cocrystal [30]. In fact, both APIs belong to the same family, and they have similar structures and pK a values, so similar dissolution rate behavior was expected.…”
Section: Intrinsic Dissolution Rate Studysupporting
confidence: 86%
“…Compared to pH 2, the percentage of dissolved Norfloxacin after 30 min of dissolution is similar in the cocrystal tablet, whereas it falls to 71% in the API tablet. This behavior has been reported for some ionizable APIs-Ciprofloxacin, among others [30]-and can be explained by the change in pH at the tablet-solution interface (pH x=0 effect) [40]. When a large amount of API is dissolved, a saturated API solution is created only at the interface with the tablet surface.…”
Section: Intrinsic Dissolution Rate Studymentioning
confidence: 57%
See 1 more Smart Citation
“…In this case, solubilities of lamotrigine-methyl paraben, lamotrigine-nicotinamide and lamotrigine-nicotinamide (monohydrate) cocrystals at 1:1 ratios and that of the lamotrigine free base in water, all having pH of ~5.5, were, respectively, 0.21, 0.30, 0.23 and 0.28 mg/mL, indicating no significant difference in solubility due to cocrystal formation. In another study, Ràfols et al [ 21 ] compared dissolution rates of a zwitterionic compound, ciprofloxacin, and its cocrystal with resorcinol under different pH conditions and observed that the parent compound dissolved faster at pH 2, while the cocrystal had somewhat higher dissolution rates in the intermediate pH conditions of 4, 5 and 5.5. However, at the intestinal pH condition of 6.5, both ciprofloxacin and the cocrystal had much lower and essentially similar solubility and dissolution rates irrespective of whether the studies were conducted in buffer or fasted state simulated intestinal fluid (FaSSIF), indicating that there were no solubility and dissolution advantages of cocrystal formation under intestinal pH conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ciprofloxaine hydrochloride has been classified as BCS class IV [ 30 ]. Several attempts for tackling CIP’s low aqueous solubility issue include salt formation [ 26 , 29 , 31 , 32 , 33 , 34 , 35 , 36 ] and amorphization [ 23 ] with less frequent cases of cocrystallization [ 36 , 37 , 38 , 39 , 40 , 41 ]. As an example, Martinez-Alejo et al studied the cocrystal of ciprofloxacin and moxifloxacin hydrochloride salts with 4-hydroxybenzoic acid as coformer.…”
Section: Introductionmentioning
confidence: 99%